Crisscross heart with dextrocardia and intact interventricular septum - P Kader Muneer; Sajeer Kalathingathodika; Govindan Sajeev Chakanalil; Manuel M Sony (Wolters Kluwer Medknow Publications, 2014)
Crisscross heart is a rare congenital heart disease characterized by a twisted atrioventricular connection, as a result of rotation of the ventricular mass along its long axis. We report an asymptomatic 48-year-old woman referred to us for evaluation of a cardiac murmur. Further evaluation showed situs solitus, dextrocardia with normal atrioventricular and ventriculoarterial connection, and a crisscross relation of the atrioventricular valves. Unlike the usual case of crisscross heart, our patient had an intact ventricular septum.